THE RELATIONSHIP MARKETING PERSPECTIVE : COMPETITIVE MARKETING STRATEGY IMPLEMENTATION IN IMPROVING COMPANY PERFORMANCE - Amien, Neneng Nurbaeti (2020)
In this era of globalization, competition in the marketing sector is getting tighter and tighter. This requires knowledge of competitive marketing strategies so that an organization or company can continue to grow and improve its business performance for the long term. Relationship Marketing is one of the main functions in achieving marketing objectives tersebut. Hubungan company can create value for customers and profits for the company by way of conducting a series of relational exchange with a view of history and the future. This study uses a qualitative approach using literature study methods by collecting materials in accordance with the object of research.